Understanding taurine CNS activity using alternative zebrafish models. (December 2017) - Mezzomo, Nathana J.; Fontana, Barbara D.; Kalueff, Allan V.; Barcellos, Leonardo J.G.; Rosemberg, Denis B.
Highlights: Taurine has pleiotropic effects in brain, but its exact mechanisms are obscure. The use of alternative models to assess the CNS mechanisms of taurine is discussed. Zebrafish models of brain disorders are emergent in translational neuroscience. Zebrafish is an interesting model organism to assess the neurophysiology of taurine. Abstract: Taurine is a highly abundant "amino acid" in the brain. Despite the potential neuroactive role of taurine in vertebrates has long been recognized, the underlying molecular mechanisms related to its pleiotropic effects in the brain remain poorly understood. Due to the genetic tractability, rich behavioral repertoire, neurochemical conservation, and small size, the zebrafish ( Danio rerio ) has emerged as a powerful candidate for neuropsychopharmacology investigation and in vivo drug screening. Here, we summarize the main physiological roles of taurine in mammals, including neuromodulation, osmoregulation, membrane stabilization, and antioxidant action. In this context, we also highlight how zebrafish models of brain disorders may present interesting approaches to assess molecular mechanisms underlying positive effects of taurine in the brain. Finally, we outline recent advances in zebrafish drug screening that significantly improve neuropsychiatric translational researches and small molecule screens.